Good and beautiful and kind : becoming whole in a fractured world - Villodas, Rich (WaterBrook, 2022)
"An invitation to love like Jesus and step beyond distraction and division into the joy we long to experience--from the author of The Deeply Formed Life, winner of the Christianity Today Book Award"--